Retrospective study on outcome of macular hole surgery - Singh, S; Byanju, R; Pradhan, S; Lamichhane, G (Nepalese Journal of Ophthalmology, 2017)
Introduction: Macular hole is a common and treatable cause of central visual loss. Classic macular hole surgery consists of vitrectomy, posterior vitreous cortex removal and intraocular gas tamponade, but during the past decade focus has especially been on internal limiting membrane (ILM) peeling as adjuvant therapy for increasing closure rates. Objective: To determine and evaluate anatomical and visual outcome of macular hole surgery. Materials and methods: Retrospective analysis of all cases of macular hole surgery done by single surgeon between 2014 -2015. Results:16 eyes were analysed with follow up of 3 months. Macular hole closure after vitrectomy was 75% with visual improvement of two or more line in 62.5%.Post surgical complication included cataract 18.8%, Increased IOP 12.5% and retinal detachment 6.2%. Conclusion: Vitrectomy along with ILM peeling and Gas Tamponade with effective positioning improves in visual acuity and achieve hole closure in people with macular hole.